2014
DOI: 10.1016/j.yebeh.2014.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in seizure types and symptoms

Abstract: Background Despite the increasing interest in sex differences in disease manifestations and responses to treatment, very few data are available on sex differences in seizure types and semiology. The Epilepsy Phenome/Genome Project (EPGP) is a large-scale, multi-institutional, collaborative study that aims to create a comprehensive repository of detailed clinical information and DNA samples from a large cohort of people with epilepsy. We used this well-characterized cohort to explore differences in seizure type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
(42 reference statements)
1
16
2
1
Order By: Relevance
“…The higher reporting of precipitating factors by our female patients may be related to their having an additional factor related to hormonal changes during menstruation causing changes in seizure frequency in association with menstrual cycles [28]. It is also plausible that differences in both brain-derived and systemically derived estrogens between sexes may lead to differences in responses to the inciting event of the seizure [29].…”
Section: Seizures Pattern and Controlmentioning
confidence: 82%
See 1 more Smart Citation
“…The higher reporting of precipitating factors by our female patients may be related to their having an additional factor related to hormonal changes during menstruation causing changes in seizure frequency in association with menstrual cycles [28]. It is also plausible that differences in both brain-derived and systemically derived estrogens between sexes may lead to differences in responses to the inciting event of the seizure [29].…”
Section: Seizures Pattern and Controlmentioning
confidence: 82%
“…While differences in symptom reporting based upon sex are due to psychological, biological, or sociological factors remain unclear, the impact of one or all of these factors on epilepsy is points requiring further study [29].…”
Section: Seizures Pattern and Controlmentioning
confidence: 99%
“…Overall, no gender difference was found in localization-related epilepsy, but symptomatic localization-related epilepsies were found to be more frequent in men, while cryptogenic localization-related epilepsies were found to be more frequent in women [ 113 ]. Carlson et al [ 115 ] with the Epilepsy Phenome/Genome Project (EPGP) showed differences in several subjective ictal symptoms between males and females. The authors of these studies were not able to assess the neurobiological basis of such sex differences and could not completely rule out the possibility that the findings were biased by differences in symptom reporting and recognition; however, it is undeniable that they raise important questions about the differences that exist between sexes at the CS level.…”
Section: Epilepsymentioning
confidence: 99%
“…Sex differences have also been identified in the age of onset of brain diseases such as schizophrenia, where males develop symptoms between 18 and 25 years of age whereas females develop symptoms between 25 and 35 years (Ochoa et al, 2012 ). Moreover, reported atonic seizures in epilepsy are more frequent in males compared to females (6.5 vs. 1.7%; Carlson et al, 2014 ). These sex differences in diseases may be the result of tissue-specific differential gene expression between males and females.…”
Section: Introductionmentioning
confidence: 98%